Monetáris politikai kihívások a szubszaharai régióban: rövid számvetés és jövőbetekintés - Pásztor, Szabolcs (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
The monetary policy of the Sub-Saharan countries is a lesser-known field for those Hungarian readers who are interested in Africa. In the last few decades several fundamental changes took place so a short synthesis is badly needed to better understand this issue. Apart from the fact that this study tries to shed light on the monetary policy challenges of different periods, it also places much emphasis on the contemporary issues in central banking. After the turn of the new millenium the central banks have been struggling with unpredictable fiscal policies, the appropriate treatment of the revenues of the natural resources, not to mention the inflow of foreign aid. It is also highly important to monitor the frequency of the supply shocks and the efficiency of the monetary transmission mechanism. After shedding more light on these issues, the paper tries to focus on the role of the exchange rates, the room for manoeuvre of the central banks in the financial stability and the adequate management of the revenues stemming from the export of natural resources.